A review of hybrid photovoltaic/ thermal systems - Sredenšek, Klemen (JET on-line, 2019)
The primary objective of this paper is to review state-of-the-art hybrid photovoltaic/thermal systems and their performance analysis. The paper is designed to facilitate the comparison and evaluation of results obtained by other authors. The review was carried out for different types and designs of photovoltaic/thermal modules in indoor and outdoor conditions, as well as for different cooling types and materials.
Keywords: collector type; coolant type; electrical/thermal efficiency; hibridni termoelektrični sistemi; photovoltaic/thermal systems; učinkovitost